Politics and poetics of belonging - Guirat, Mounir (Cambridge Scholars Publishing, 2018)
The contributions gathered in this volume bear witness to the fact that belonging is a multi-faceted concept that necessitates different and shifting idioms of expression. It continually requires reconsideration and redefinition of our affiliations in response to the rapid social, cultural, and political changes of our world. The literary paradigms, linguistic practices, and cultural formations of belonging testify to the impossibility of confining it to conventional and established structures of knowledge. The different reflections on belonging introduced in this book are instrumental in reas.